Trypanosoma vivax infections: pushing ahead with mouse models for the study of Nagana. II. Immunobiological dysfunctions. - Marie Christine Blom-Potar; Nathalie Chamond; Alain Cosson; Grégory Jouvion; Sabrina Droin-Bergère; Michel Huerre; Paola Minoprio (Public Library of Science (PLoS), 2010)
Trypanosoma vivax is the main species involved in trypanosomosis, but very little is known about the immunobiology of the infective process caused by this parasite. Recently we undertook to further characterize the main parasitological, haematological and pathological characteristics of mouse models of T. vivax infection and noted severe anemia and thrombocytopenia coincident with rising parasitemia. To gain more insight into the organism's immunobiology, we studied lymphocyte populations in central (bone marrow) and peripherical (spleen and blood) tissues following mouse infection with T. vivax and showed that the immune system apparatus is affected both quantitatively and qualitatively. More precisely, after an initial increase that primarily involves CD4(+) T cells and macrophages, the number of splenic B cells decreases in a step-wise manner. Our results show that while infection triggers the activation and proliferation of Hematopoietic Stem Cells, Granulocyte-Monocyte, Common Myeloid and Megacaryocyte Erythrocyte progenitors decrease in number in the course of the infection. An in-depth analysis of B-cell progenitors also indicated that maturation of pro-B into pre-B precursors seems to be compromised. This interferes with the mature B cell dynamics and renewal in the periphery. Altogether, our results show that T. vivax induces profound immunological alterations in myeloid and lymphoid progenitors which may prevent adequate control of T. vivax trypanosomosis.